2020
DOI: 10.1002/jcp.29577
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circTET3 mediates migration of rat vascular smooth muscle cells by targeting miR‐351‐5p

Abstract: Abnormal migration and proliferation of vascular smooth muscle cells (VSMCs) are the pathological basis of hyperplasia during vein graft disease. It remains unknown if circular RNAs (circRNAs) are involved in vein graft disease. In the present study, a rat vein graft model was constructed by the "cuff" technique, and whole transcriptome deep sequencing was applied to identify differential circRNAs in the grafted vein compared to the control. We identified a novel circRNA, named circTET3, whose structure was ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…39 In addition, circTET3 can mediate migration of rat vascular smooth muscle cells by targeting miR-351-5p. 40 These lines of evidence indicated that the molecules in this network are highly correlated with GC, and both play a role by targeting miRNA. Intriguingly, most of them showed distinct differences in expression after EBV infection.…”
Section: Dovepressmentioning
confidence: 95%
“…39 In addition, circTET3 can mediate migration of rat vascular smooth muscle cells by targeting miR-351-5p. 40 These lines of evidence indicated that the molecules in this network are highly correlated with GC, and both play a role by targeting miRNA. Intriguingly, most of them showed distinct differences in expression after EBV infection.…”
Section: Dovepressmentioning
confidence: 95%
“… 205 Similarly, circRNAs also regulate vascular cells in ISR. circRNAs mediate EC proliferation (hsa_circ_0003575) 211 and migration (circ_0003204), 212 as well as VSMC proliferation (circ_Lrp6), 213 migration (circTET3), 214 and phenotypic transformation (circ-SATB2). 215 In the future, ISR may be treated by targeting circRNAs.…”
Section: Main Textmentioning
confidence: 99%
“…It is therefore not surprising that deregulated expression of circRNAs is closely related to different types of diseases, such as degenerative diseases, tumor, congenital diseases, endocrine diseases and cardiovascular diseases ( Lukiw, 2013 ; Li et al, 2019a ; Chen et al, 2021a ; Li et al, 2021 ; Papatsirou et al, 2021 ). With relevance to clinical practice, tissue circRNAs could act as potential biomarkers for prognostication and diagnosis of diseases, particularly tumors ( Hu et al, 2019 ; Liu et al, 2020 ; Yao et al, 2020 ; Luo et al, 2021 ). Recently, several studies demonstrated that aberrant circRNA expression could contribute to the deregulated migration and proliferation of VSMCs ( Qin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%